Pulmonary aspiration in pediatric anesthetic practice in the UK: a prospective survey of specialist pediatric centers over a one-year period - Walker, Robert W.M. (Pediatric anesthesia, 2013)
Summary Background Pulmonary aspiration of gastric contents is a potentially devastating complication of anesthesia. Aims This prospective multicenter survey of specialist pediatric centers in the UK set out to elucidate the incidence, risk factors, and the outcome of such events. The survey took place over a twelve‐month period via a web‐based secure reporting system. Results Over the twelve‐month period, 24 cases of pulmonary aspiration were reported. Over that time period, there were 118 371 cases performed at the eleven pediatric centers. The overall incidence of pulmonary aspiration is therefore 1 in 4932 cases or 2 in 10 000 cases. Over that time period, there were 18 cases during elective surgery and six cases in nonelective/emergency surgery. The incidence of pulmonary aspiration in the elective situation is therefore 1 in 5076 cases or 2.0 per 10 000 cases. The incidence in emergency procedures is 1 in 4498 cases or 2.2 per 10 000 cases. The timing and severity of deterioration were recorded. In the study period, 8 of 24 cases did not deteriorate, 13 of 24 deteriorated with immediate effect, and the further 3 of 24 deteriorated within the next hour. The deterioration was mild in 11 patients requiring medical management only, and the deterioration was severe in five patients. Those five patients required ventilation for varying durations of time. All patients made a full recovery. Conclusions This multicenter survey of specialist pediatric centers in the UK over a one‐year period reveals a low incidence of pulmonary aspiration in both elective and emergency cases. All patients made a full recovery.